2017
DOI: 10.1016/j.ijscr.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine sweat gland adenocarcinoma: A rare case report and review

Abstract: HighlightsApocrine Sweet Gland Adenocarcinoma is a very uncommon cancer that can cause structural deformities by metabolic disorder (paraneoplastic syndrome).That’s the first case related on Brazil.This case contributes to the best choice of the exams required for detection of this rare cancer (there is no consensus in the literature by the limited number of cases).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
9
0
4
Order By: Relevance
“…Apocrine carcinoma usually appears as a single, small nodule or a multinodular mass which is characterized by symptomatic progression. The incidence of Primary Apocrine Sweat Gland Carcinoma (PASGC) is quite low at 0.0049 to 0.0173 cases/100,000 persons per year [3,4]. These types of carcinomas comprises tumors with varied biological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Apocrine carcinoma usually appears as a single, small nodule or a multinodular mass which is characterized by symptomatic progression. The incidence of Primary Apocrine Sweat Gland Carcinoma (PASGC) is quite low at 0.0049 to 0.0173 cases/100,000 persons per year [3,4]. These types of carcinomas comprises tumors with varied biological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment for PASGC is local excision with a clear margin of 1–2 cm along with ALND if clinically positive nodes are detected. It is considered that the most important predictor of survival may be lymph node metastasis (40–60%) [ 2 , 3 , 9 , 10 ]. Therefore, accurate diagnosis of lymph node metastasis is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, accurate diagnosis of lymph node metastasis is necessary. The benefit of ALND for clinically node negative PASGC patients is unclear [ 1 , 10 ]. Previous studies have shown that SLNB was useful for those patients [ 6 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of apocrine adenocarcinoma is approximately one in 6-20million patients per year [4]. The median patient age is 67 without racial or gender preference [4,5]. They are found in areas of high apocrine sweat gland density, mainly in the axilla and anogenital region, but also reported in the eyelid, scalp, nipple, lip, and others [4,5,[9][10][11][12].…”
Section: Case Discussionmentioning
confidence: 99%
“…The malignant counterpart is apocrine adenocarcinoma, a rare entity found in areas of high apocrine gland density, mainly in the axilla and anogenital region. However, there have been cases in the eyelid arising from Moll's glands, scalp, nipple, lip, and others [2][3][4][5]. Co-occurrence of apocrine adenocarcinoma and hidrocystoma is extremely rare and has only been reported in 5 cases [6].…”
Section: Introductionmentioning
confidence: 99%